Hyper‐planning Jakarta: The Great Garuda and planning the global spectacle. Issue 1 (5th September 2018) - Wade, Matt
Abstract : After a major flood in Jakarta in 2007, the government of Indonesia partnered with a consortium of Dutch engineers and designers to produce a solution. In 2013, this consortium proposed a plan for the Great Garuda, a megaproject that combined a deep seawall and private real estate, both in an archipelago of reclaimed islands that would be shaped like the mythical garuda eagle, Indonesia's national symbol. Despite a range of infeasibilities and opposition, the Great Garuda became the most prominent vision for the city's future. This article argues that the promotion of the Great Garuda was a process of 'hyper‐planning', which projected the city as a national triumph and a global spectacle. The plan served the political objective of creating the mere possibility of a 'new Jakarta' apart from the perceived chaos of the current capital. Further, the plan functioned as a performative object through its iconic imagery and its circulations. The process of hyper‐planning simultaneously projected a future of urban success, but also displaced the contingencies of the future to the private sector, beyond the purview of the state.